Accumulating Foreign Reserves Under Floating Exchange Rates - Goncalves, Fernando M. (IMF Working Papers; Working Paper ;, 2008)
Official accumulation of foreign reserves may be perceived as interventions to influence the exchange rate, undermining the credibility of floating exchange rates and inflation targets. This paper develops a theoretical framework to study the interaction between reserve accumulation and monetary policy. The model uncovers a trade-off between the speed of reserve accumulation and anti-inflationary credibility. Under reasonable assumptions, delegation of intervention and monetary policy decisions to separate government agencies allows faster reserve accumulation, while centralization of these decisions results in a more stable economy. The analysis underscores the importance of rather overlooked institutional features of policymaking in open economies.